Respuesta :
(3x – 5)(–x + 4)
= (3x)(–x) + (3x)(4) + (–5)(–x) + (–5)(4)
= -3x^2 + 12x + 5x - 20
= -3x^2 + 17x - 20 ......this is in standard form
= (3x)(–x) + (3x)(4) + (–5)(–x) + (–5)(4)
= -3x^2 + 12x + 5x - 20
= -3x^2 + 17x - 20 ......this is in standard form
By using the distributive property, we will see that the simplified product is:
-3x^2 + 17x - 20
How to distribute a product?
The distributive property says that:
A*(B + C) = A*B + A*C
Then, if we apply that to our product, we get:
(3x - 5)*(-x + 4)
(3x)*(-x) -5*(-x) + (3x)*4 - 5*4
Simplifying that we get:
-3x^2 + 5x + 12x - 20
-3x^2 + 17x - 20
So the simplified product in standard form is just:
-3x^2 + 17x - 20
If you want to learn more about properties, you can read:
https://brainly.com/question/2475734